Dampak Zis, Korupsi, Dan Pendidikan Terhadap Tingkat Ketimpangan Pendapatan di Negara Berkembang: Studi Kasus di Indonesia - Ramadhansyah Rayyan Effendy; Verina Araminda Prinary; Cupian Cupian; Ardi Apriliadi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study seeks to examine and assess the influence of Zakat, Infaq, and Sedekah (ZIS), corruption, and education on income inequality in Indonesia. The research uses a saturated sampling method, collecting data from the National Zakat Amil Agency (BAZNAS), Transparency International, the Central Statistics Agency (BPS), and the World Bank. The analysis uses quantitative time-series data from 2011 to 2022, processed with Stata 15, and employs multiple linear regression as the analytical method. The results indicate that ZIS has a significant negative effect on income inequality, while corruption also significantly reduces income inequality. On the other hand, education shows a positive but statistically insignificant effect. The coefficient of determination test reveals that 93.06% of the variation in income inequality can be explained by ZIS, corruption, and education, with the remaining 6.94% attributed to other factors not included in the study. Additionally, the findings suggest that ZIS and corruption together have a notable influence on income inequality.